Learning to Think Like an Economist without Becoming One: Ambivalent Reproduction and Policy Couplings in a Masters of Public Affairs Program - Hallett, Tim; Gougherty, Matthew (American Sociological Review, 2024)
In recent years, sociologists have labored to understand how economists have gained influence over policymaking. We extend this research by shifting focus from the matter of influence to the matter of policy training. Granted that economists already have influence, how do future policy professionals learn economic rationales? How is this mindset transmitted to hesitant students? By asking these questions, we bring socialization back into institutional research on “new” professionals. Utilizing data from an ethnography of a Masters of Public Affairs program, we find that students learn economics through a process of “ambivalent reproduction”: they learn to “think like an economist without becoming one.” They remain skeptical and reject the notion that they are economists, and when they use economics in their future policy work they do so in limited ways. Nonetheless, ambivalent reproduction sustains the policy status-quo and allows economics to remain influential without true belief. Ambivalent reproduction provides a new means for understanding the loosely coupled influence of economics on policy, and it contributes to the sociology of economics, inhabited institutionalism, and professional socialization.